Effectiveness of Technical Skills Attacking Senior Athlete Kyourugi at the 2023 World Taekwondo Championship in Baku, Azerbaijan - Nopi Hariadi; Soetanto Hartono; Achmad Widodo; Heryanto Nur Muhammad; Donny Setiawan (IKIP Widya Darma Surabaya, 2023)
Abstract Objective: The aim of this study is to find out the level of effectiveness of attack techniques used by senior athletes Kyourugi at the 2023 World Taekwondo Championship in Baku, Azerbaijan. As for the participants in this study, 32 Kyurugi athletes consisted of 16 male and 16 female athlete with the criteria of all athlets entering the final in each competitive class. Method: The data collection uses quantitative descriptives by observing the video of the game in the final. Results: The results of the effective kick used in competition by senior Taekwondo athletes male and female based on the top 6 rankings are Peta Chagi male Kyourugi athlete of 49.5%, and female Kyourugi athlete of 69.9%, Dollyo Chagi male Kyourugi athlete of 33.7% and the female Kyourugi athlete of 31.5%, Ceking Yeop Chagi male Kyourugi athlete of 22.3%, and the Female Kyourugi athlete of 18.1%, punch (Jireugi) male Kyourugi athlete of 10.6%, and female Kyourugi Athlete of 5.6%, Pyojeuk Chagi male Kyourugi athlete of 8.2% and female Kyourugi athlete of 2.6% and Deol Chagi male Kyourugi athlete of 6.7% and female Kyourugi athlete of 8.4%. Novelty: The most effective taekwondo kicking techniques used by senior Kyourugi athlete male and femaler to attack during competition are the Peta Chagi kicking, and the punch techniqu (Jireugi).